ANALISIS PERBANDINGAN PORTOFOLIO OPTIMAL MENGGUNAKAN GRAHAM SELECTION DENGAN PORTOFOLIO OPTIMAL SINGLE INDEX MODEL TERHADAP SAHAM-SAHAM LQ 45 PERIODE 2000-2010 - , Luthfia Rahmani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is an empirical study that aims to analyze the performance of optimal portfolio which are formed by the method of Graham compared to the performance of optimal portfolio which are formed by the Single Index Model (SIM) and measured by using Sharpe Index, Treynor Index, Jensen Index and RDIV. The sample was selected by purposive sampling method with filtering a list of stocks LQ 45 used is the period of August 2010 till January 2011, while the period of time to capture the required data starting in 2000 till 2010. The analysis showed that the method of Single Index Model is able to provide return of portfolio better than the methods of Benjamin Graham. Optimal portfolio which are formed by the method of Benjamin Graham obtained an average of portfolio expected return of 0.2% with the varian (risk) portfolio of 0.07%.While the SIM portfolio expected return obtained by 0.36% with the varian (risk) portfolio of 0.05%. Similarly, results of the assessment of portfolio performance that is using risk adjusted return index including Sharpe, Treynor, Jensen Index and viewed from the ability to diversify risks by using measurements of Reward to Diversification (RDIV), shows that the portfolio Single Index Model superior to Graham.